PETIT BLACK VELVET CAKE BASED BLACK RICE FLOUR HIGH FIBER - Sri Palupi, Siti Nurhalizah (Prosiding Pendidikan Teknik Boga Busana, 2020)
In 2016 imports of wheat for consumption needs in Indonesia based on Statistical Center Data (BPS) of 8.3 million tons annually. Therefore, researchers make a product based on local food that is black rice to suppress the number of grain imports in Indonesia. The study aims to find the Petit Black Velvet formula that can be accepted by the community. This research uses the Research and Development (R&D) method with the development model 4D (Define, Design, Develop and Disseminate). In this study, Petit Black Velvet with a variable composition of black rice flour using 30%, 50% and 70% substitution. The results showed that the Petit Black Velvet product that is acceptable to the public is by substitutions of black rice flour for 70%, with a reference recipe from Jobsheet Patisserie I Boga UNY. From the test results with untrained panelists showed that the overall average value of 3.75 means that the Petit Black Velvet product is already acceptable to the community. Keywords: Petit Black Velvet Cake, black rice flour, high fiber